Resolvin D1 Modulates the Intracellular VEGF-Related miRNAs of Retinal Photoreceptors Challenged With High Glucose - Maisto, Rosa; Trotta, Maria Consiglia; Petrillo, Francesco; Izzo, Sara; Cuomo, Giovanna; Alfano, Roberto; Hermenean, Anca; Barcia, Jorge Miquel; Galdiero, Marilena; Platania, Chiara Bianca Maria; Bucolo, Claudio; D’Amico, Michele (Frontiers in Pharmacology, 2020)
Abstract Stimulation of retinal photoreceptors with elevated glucose concentration (30 mM) for 96 hours, served as diabetic retinopathy in-vitro model to study Resolvin D1 (50 nM) effects on neovascularization. VEGF and anti-angiogenic miR-20a-3p, miR-20a-5p, miR-106a-5p and miR-20b expression was assessed either in photoreceptors exposed to HG or in exosomes released by those cells. High glucose increased VEGF levels and concurrently decreased anti-angiogenic miRNAs content in photoreceptors and exosomes. RvD1 reverted the effects of glucose damage in photoreceptors and exosomal pro-angiogenic potential, tested with the HUVEC angiogenesis assay. By activating FPR2 receptor, RvD1 modulated both the expression of anti-angiogenic miRNA, which decrease VEGF, and the pro-angiogenic potential of exosomes released by primary retinal cells. HUVEC transfection with miR-20a-3p, miR-20a-5p, miR-106a-5p and miR-20b antagomirs, followed by exposure to exosomes from photoreceptors, confirmed the VEGF-related miRNAs mechanism and the anti-angiogenic effects of RvD1.